Paparan mikroplastik PVC dalam air induk mengurangi pembuahan, penetasan, dan kelangsungan hidup ikan zebra - Teguh Bachtiar; Bagus Dwi Hari Setyono; Yuliana Asri (Universitas Mataram, 2026)
This study evaluated the effect of polyvinyl chloride (PVC) microplastic exposure through broodstock rearing water on the fertilization rate (FR), hatching rate (HR), and survival rate (SR) of zebrafish (Danio rerio). Fish were exposed for 30 days in a completely randomized design with four PVC doses, namely 0, 5, 10, and 15 mg/L, each with three replicates. After exposure, broodstock were spawned to obtain FR and HR data, whereas SR was calculated during the rearing period. One-way ANOVA showed that PVC dose significantly affected FR (F(3,8)=53.48; P<0.001), HR (F(3,8)=70.44; P<0.001), and SR (F(3,8)=9.33; P=0.005). Duncan’s multiple range test separated all FR and HR treatments into different homogeneous subsets, indicating a clear dose-related decline. FR decreased from 90.83% in the control to 68.43% at 15 mg/L, whereas HR declined from 94.77% to 75.17%. SR showed a more moderate pattern: the control, 5 mg/L, and 10 mg/L remained in the same homogeneous subset, while 15 mg/L formed a distinct subset with a mean of 81.67%. Water quality remained relatively stable during the experiment, with temperature at 29.1-29.3 °C, pH at 8.29-8.49, and dissolved oxygen at 7.0-7.5 mg/L. These findings indicate that, under the present experimental conditions, early reproductive endpoints were more sensitive to PVC microplastic exposure than survival.